Pengaruh Work Life Balance dan Organizational Trust terhadap Employee Performance melalui Work Engagement pada Karyawan - Nadila Puteri Ayuningtyas; Budiono (Jurnal Ilmu Manajemen, 2025)
Bank X, an operational branch located in Sidoarjo Regency, is part of a state-owned enterprise that specializes in banking services and housing finance. This study aims to identify and explain the influence of work-life balance and organizational trust on employee performance, with work engagement as a mediating variable, among the employees of Bank X in Sidoarjo. This research applies a quantitative method. The sampling technique used is non-probability sampling with purposive sampling, involving 55 employees of Bank X. The data in this study were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.2.9 software. The result work-life balance does not have a significant effect on either employee performance or work engagement. Organizational trust also does not directly affect employee performance, but it has a significant and positive influence on work engagement. Furthermore, work engagement has a significant and positive impact on employee performance. Work engagement does not mediate the relationship between work-life balance and employee performance, but it does mediate the effect of organizational trust on employee performance.